Bilateral atypical lamellar holes in a patient with oculocutaneous albinism. (2nd September 2020) - Falcone, Michelle M.; Patel, Nimesh A.; Yannuzzi, Nicolas A.; Acon, Dhariana; Negron, Catherin I.; McKeown, Craig; Berrocal, Audina M.
ABSTRACT: Background: Albinism can present with a wide range of ophthalmic findings and variable expressivity. With the use of optical coherence tomography, there has been increasing awareness of the variability of macular findings in this condition. Materials and Methods: Case report Results: We present a case of oculocutaneous albinism with bilateral atypical lamellar holes which may represent part of the spectrum of retinal abnormalities in this condition. Conclusion: Optical coherence tomography can be helpful in diagnosing albinism. Variable expressivity leads to a range of macular pathology in albinism which may include atypical lamellar holes as described in this patient.